A paradox rarely comes alone a quantitative approach to investigating knotted leadership paradoxes in SMEs. Issue 1 (March 2021) - Henriksen, Thomas Duus; Nielsen, Rikke Kristine; Vikkelsø, Signe; Bévort, Frans; Mogensen, Mette
Highlights: Management paradoxes intertwine into knotted paradoxes. Dealing with organisational fragmentation is a significant challenge to SME managers. Managing engagement and control has a suppressive effect onto other paradoxes. Organisational distribution is a current and perhaps future performance challenge. Abstract: This article uses a paradox knotting perspective to study key leadership challenges among Danish manufacturing and crafting SMEs. As part of an action-learning development programme, 55 middle managers from 11 companies were asked to rate the topicality of 10 leadership paradoxes. Using exploratory factor analysis, three clusters of knotted paradoxes were identified concerning the management of 1) managing organisational flexibility, 2) balancing engagement and control, and 3) dealing with dispersion. Each identified knot consists of two paradoxes and shows how managers involved in one element of a knotted paradox are also likely to be involved in the tensions of the other. The article contributes to a better understanding of the complexity and interrelatedness of select management paradoxes by demonstrating that paradoxes appear knotted in practice. Furthermore, the empirical and quantitative approach to studying paradoxes and their interrelatedness serves as an important methodological contribution to a field characterised by a high reliance on indirect, qualitative studies.